Relationships among lying and standing behaviour, body condition score and milk production in primiparous cows. Issue 1 (14th December 2020) - Mattachini, Gabriele; Tamburini, Alberto; Zucali, Maddalena; Bava, Luciana; Riva, Elisabetta; Provolo, Giorgio; Sandrucci, Anna
Abstract: The aim of this study was to examine the time budgets of 20 lactating primiparous Italian Holstein cows and to determine the relationships between lying and standing behaviour, milk production and Body Condition Score in the first stage of lactation. Parturition period ranged from 15 September to 31 March and in the first seven lactation days all cows were equipped with individual 3-axes acceleration and angular displacement loggers, throughout 150 days for lying and standing behaviour measuring. Body Condition Scores (BCS) were estimated weekly, while milk production (in both morning and evening milking) and humidity and temperature air data were collected daily. Average individual milk yield was 27.3 ± 6.24 kg/d and milking time was 4.95 ± 1.94 min. Individual BCS was on average 3.46 ± 0.30 and standing daily time was 13.5 ± 2.26 h/d. Primiparous cows with BCS at parturition <3.25 quite regained BCS after 20 weeks of lactation, but produced on average 2.3 kg/d ( p < .001) less than the other cows. Primiparous cows with standing time <14 h/d in the first 21 days of lactation showed higher BCS than the others cows (+0.11 on average, p < .001), but did not produce more milk (+0.1 kg/d, p = .25) on average and showed smaller Linear Score (logarithm transformation of milk somatic cell count) than other cows. Primiparous cows with standing time <14 h/d had higher number of lying bouts and less minutes between two lying bouts, probably due to a higher cow activity to feeding. Multiple regression on milk production showed a low effect of standing time, but primiparous cows lost 0.34 kg/d ( p < .05) for each standing hour. HIGHLIGHTS: Primiparous cows with standing time <14 h/d in the first 21 days of lactation showed higher BCS than the others cows Primiparous cows with standing time <14 h/d showed smaller somatic cell count Primiparous cows lost 0.34 kg/d for each standing hour